PEMANFAATAN LAW AND ECONOMICS SEBAGAI METODOLOGI ANALISIS HUKUM DI INDONESIA - Kristianus Pramudito Isyunanda (Faculty of Law, Universitas Gadjah Mada, 2022)
Abstract There are various dimensions of legal thoughts to solve and provide logical solutions for legal issues or problems. The complexity of problems that require legal solutions creates an urgency to explore interdisciplinary analysis, one of which is between legal science and economic studies. This article is to explore the available options for economic analysis of laws (law and economics as an interdisciplinary approach on laws) and their use in the Indonesian legal system. The desired state is to present an alternative methodological tool for legal studies in Indonesia. Theories, conventions, and economic principles within the law and economics framework are relevant to be methodological tools to solve legal issues in Indonesia. Abstrak Pemikiran hukum memiliki berbagai dimensi, dengan tujuan menjawab isu/permasalahan hukum serta memberikan solusi logis. Kompleksitas masalah yang memerlukan solusi hukum mendorong kebutuhan eksplorasi atas irisan interdisipliner, salah satunya antara ilmu hukum dan ekonomi. Artikel ini mengeksplorasi pilihan-pilihan analisis keekonomian tentang hukum (law and economics sebagai pendekatan interdisipliner tentang hukum) dan pemanfaatannya pada sistem hukum Indonesia. Penulisan bertujuan melengkapi khazanah metodologi analisis hukum di Indonesia. Teori, kaidah, dan prinsip ekonomi dalam kerangka law and economics relevan menjadi kacamata metodologis untuk memecahkan persoalan hukum di Indonesia.